Changes in Breast and Cervical Cancer Incidence by Stage at Diagnosis During the COVID‐19 Pandemic in Utah - Michelle Mumper; Leisha Nolen; Kimberly A. Herget; Rachel R. Codden; Marjorie E. Carter; Marie Nagata; Morgan M. Millar (Cancer Medicine)
ABSTRACT Purpose The COVID‐19 pandemic caused unprecedented disruptions in healthcare access, resulting in significant delays in breast and cervical cancer screening and diagnostic services. This study examined whether there were changes in the stage of diagnosis for breast and cervical cancers diagnosed among Utah women during the pandemic compared to years prior to the pandemic. Methods Patients included adult females with a new breast or cervical cancer diagnosis reported to the Utah Cancer Registry, diagnosed from January 2020 to December 2021 (pandemic time period) or between January 2018 and December 2019 (pre‐COVID‐19). We calculated age‐adjusted incidence rates and incidence rate ratios (IRRs) with 95% confidence intervals (CI) to compare stage at diagnosis and sociodemographic factors between time periods. Results A total of 308 cervical cancer cases and 8215 breast cancer cases were diagnosed throughout the duration of the study. Overall incidence of cervical cancer was higher during the pandemic, driven primarily by distant‐stage disease incidence, which was more than three times higher than before the pandemic (IRR, 3.11; 95% CI, 1.67–5.79). Non‐Hispanic (NH) White women were significantly more likely to be diagnosed with late‐stage cervical cancer (IRR, 1.60; 95% CI, 1.12‐2.30) during the pandemic compared to pre‐pandemic. Local‐stage breast cancer incidence decreased slightly during the pandemic compared to pre‐pandemic (IRR, 0.93; 95% CI, 0.88–0.99). Hispanic women saw a slight increase in late‐stage breast cancer incidence during the pandemic compared to before the pandemic (IRR, 1.31; 95% CI, 1.03–1.67). Conclusions We saw a significant increase in the incidence of late‐stage cervical cancer during the pandemic compared with pre‐pandemic. Conversely, while local‐stage breast cancer incidence was slightly lower during COVID‐19 compared with pre‐COVID‐19, no difference was observed among all other stages. More time is needed to assess the full impact of COVID‐19 on breast and cervical cancer trends.